Prevention of the Postthrombotic Syndrome: Where Do We Stand? - Vedantham, Suresh (Seminars in Interventional Radiology, 2025)
The postthrombotic syndrome (PTS) is a common complication of lower extremity deep vein thrombosis (DVT) that impairs patients' health-related quality of life despite the use of standard therapy. Prevention of PTS is an important goal of quality DVT care, and includes prevention of recurrent DVT with anticoagulation, use of compression therapy, mitigation of functional contributors to limb edema, use of endovascular therapy to prevent venous obstruction and valvular reflux, and reduction of inflammation within the involved veins and limb. This study reviews best practices in clinical PTS prevention, clinical trial evidence on endovascular therapy outcomes, and mechanistic observations about PTS with the goal of preparing the interventional radiology physician to deliver outstanding patient care and to lead local and national multi-specialty initiatives that are aimed at PTS prevention.
Keywords: deep vein thrombosis; postthrombotic syndrome; thrombolysis; thrombectomy; pharmaco-mechanical; interventional radiology